Accuracy of determining sarcopenia using SARC-CalF in community-dwelling older adults aged 75 years and older. (December 2022) - Ishimoto, Taisei; Hisamatsu, Ken; Matsudaira, Nozomi; Fujimoto, Takehiro; Yano, Manoka; Hashimoto, Risako; Hayashi, Hikaru; Toyota, Yoshio; Akazawa, Naoki
Summary: Objective: The accuracy of sarcopenia determination using SARC-CalF in community-dwelling older adults has been clarified in previous studies. However, this accuracy is unknown for subjects older than 75 years old. If this becomes clear, it will show the usefulness of using SARC-CalF in determining sarcopenia in community-dwelling older adults aged ≥75 years old. Thus, this study aimed to investigate the accuracy of sarcopenia determination using SARC-CalF in community-dwelling older adults aged ≥75 years old. Methods: This study included 102 older adults aged ≥75 years old (74.5% female). Subjects were provided outpatient rehabilitation one to three times a week. The Asia Working Group for Sarcopenia 2019 standard was used to determine sarcopenia in participants. Logistic regression analysis was performed with sarcopenia as the dependent variable, and age, sex, and SARC-CalF as independent variables. When SARC-CalF was extracted as a significant variable, a receiver operating characteristic (ROC) curve was created. The cut-off value was calculated using the Youden index. Results: Sarcopenia was observed in 65 of 102 subjects. Logistic regression analysis showed that only SARC-CalF was extracted as a significant variable (odds ratio: 1.18 [95% CI: 1.09–1.29]). The cut-off value calculated from the ROC curve was seven points. The sensitivity and specificity were 94.7% and 92.3%, respectively, and the area under the curve was 0.98. Conclusions: Our results indicate that SARC-CalF can accurately determine sarcopenia in older adults. A SARC-Calf cut-off value of seven may be more useful than 11 in determining sarcopenia in community-dwelling older adults aged ≥75 years old. Highlights: Sarcopenia was found in 63.7% of community-dwelling older adults aged ≥75 years old who are using outpatient rehabilitation. SARC-CalF can determine sarcopenia in elderly individuals with high accuracy. SARC-CalF cut-off value of seven points may be more useful than 11 points in determining sarcopenia in community-dwelling older adults aged ≥75 years old.